[No more Sabado nights] - Coronel, Shiela; Magsanoc, Kara.; Rimban, Luz.; Philippine Center for Investigatures Journalism (Quezon City The Center, 1996)
Tells the story of how the women of Tawid Sapa, a slum in Novaliches, organized themselves against wife-beating, set up refuge for battered women, and even got the government to install electric lines and deep wells in their community.
Title on cover : No more Sabado nights.
VHS.
Also available in VCD format.
Keywords: Women -- Identity; Family violence -- Philippines -- Novaliches; Poor -- Philippines -- Novaliches; Women -- Services for -- Philippines; Women's rights -- Philippines -- Novaliches; Philippines -- Social Conditions